The disinfectant effect of modified hydrothermal nanotitania extract on candida albicans - Nor Farid Mohd Noor; Mohamad Ezany Yusoff; Mohd Azizi Abdul Rahman; Mohammad Khursheed Alam; Ahmad Mukifza Harun (Hindawi Publishing Corporation, 2021)
Candida albicans is a pathogenic yeast typically associated with diseases such as HIV, AIDS, and other immunocompromised conditions. It is rarely the cause of fatalities and is commonly treated with drugs administered orally or intravenously. In this experiment, Candida albicans was tested with an extract of modified hydrothermal nanotitania to identify whether the material is capable of inhibiting the organism’s growth. The extract was mixed with the Candida albicans in a culture media preparation to determine whether the organisms were able to grow. The test showed that modified hydrothermal nanotitania inhibits the growth of this organism.